Literature Study: The Role of Effective Human Resource Management in Improving the Quality of Health Services - Dewi Agustina; Nadilla Fitri Yanni; Aura Dwi Rahman; Layla Maznun Br Ginting; Hasnah Aullia; Adinda Mulpira Br Tanjung; Mutya Purnama Ramadhani; Nadya Elya Syahraini Br Saragih; Nazla Ayumna Putri; Ummu Mawaddah Ikrimah Damanik; Audya Putri Az-Zahra; Nur Indah Hasibuan (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The quality of healthcare is one of the main indicators of the success of a national healthcare system. However, to date, many healthcare facilities still face challenges in maintaining service quality and patient satisfaction due to weak human resource management. This study aims to analyze the role of effective human resource management in improving healthcare quality and patient satisfaction. The method used is a literature study by reviewing eight national and international journals published in the last five years. The results of the review show that the effectiveness of HR management has a significant influence on the quality of health services. The main factors that contribute to increased patient satisfaction include the competence of health workers, professional attitudes, work motivation, continuous training, performance appraisal systems, and good HR management. Effective HR management has been proven to increase productivity, improve communication between health workers and patients, and create a positive work environment. Conversely, weak HR management has an impact on low service quality and patient satisfaction. Therefore, the implementation of planned, sustainable, and competency-based HR management strategies is an important step in realizing quality, efficient, and patient-oriented health services.